Mechanochemical preparation of triptolide-loaded self-micelle solid dispersion with enhanced oral bioavailability and improved anti-tumor activity - Dabu Zhu; Qiuqin Zhang; Yifang Chen; Minghua Xie; Jianbo Li; Shen Yao; Ming Li; Zhao Lou; Yue Cai; Xuanrong Sun (Taylor & Francis Group, 2022)
Triptolide (TP), a compound isolated from a Chinese medicinal herb, possesses potent anti-tumor, immunosuppressive, and anti-inflammatory properties, but was clinically limited due to its poor solubility, bioavailability, and toxicity. Considering the environment-friendly, low-cost mechanochemical techniques and potential dissolution enhancement ability of Na2GA, an amorphous solid dispersion (Na2GA&TP-BM) consisting of TP and Na2GA were well-prepared to address these issues. The performance of Na2GA&TP-BM was improved through ball milling, such as from crystalline state to an amorphous solid dispersion, suitable nano micelle size and surface potential, and increased solubility. This change had a significant improvement of pharmacokinetic behavior in mice and could be able to extend the blood circulation time of the antitumor drug. Moreover, in vitro and in vivo anti-tumor study showed that Na2GA&TP-BM displayed more potent cytotoxicity to tumor cells. The work illustrated an environment-friendly and safe preparation of the TP formulation, which was promising to enhance the oral bioavailability and antitumor ability of TP, might be considered for efficient anticancer therapy.